Analysis Disaster Vulnerability Capacity in Mempawah Hilir Subdistricts - Nunik Hasriyanti; Andi Zuletstari; Ismail Ruslan; Lestari Agustrihardaning (Department of Architecture Universitas Muhammadiyah Jakarta, 2019)
Data in the West Kalimantan Figures (BPS) in 2010, there were 34 sub-districts in the West Kalimantan coastal area with a total area of 20,066 Km2 and a population of 1,100,000 people or 25% of the projected total of 4.4 million residents of West Kalimantan. Means that people who live in coastal areas including small islands have become the majority concentration on the distribution of the population of West Kalimantan, while having a close relationship with access to potential marine and coastal resources and environmental use. In the Strategic Plan of the West Kalimantan Regional Disaster Management Agency 2013-3018 (2) states that the inhibiting and driving factors are in disaster management in West Kalimantan due to the absence of hazard-prone mapping and safe disaster mapping, especially in coastal areas. The purpose of this research is to find out and analyze the level of disaster vulnerability in the District of Mempawah Hilir. The data collection method used is to determine aspects and indicators of capacity assessment of disasters in the District of Mempawah Hilir. From the results of the assessment of factors A to factor E, it can be concluded that the level of capacity of each village in Mempawah District is still very low. This low capacity value is dominated in villages in Sungai Kunyit and Siantan Districts. Villages that have moderate capacity value are Kuala Secapah Village, Pasir Village, Sengkubang Village and Jungkat Village. Overall villages in Mempawah sub-district are still low on the early warning factor and disaster risk assessment and preparedness development factors on all lines.